Kajian Keunggulan Komparatif dan Strategi Pengembangan Kerbau Rawa Di Kalimantan Selatan - Ahmad Suhaimi; Zarmiyeni Zarmiyeni; Azwar Saihani; Rum Van Royensyah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2016)
Swamp buffalo in South Kalimantan is a potential commodity in terms of providing meat because its ability to digest crude fiber is better than cattle with low quality feed conditions, and has the ability to reproduce over a wide range from wet areas to relatively dry areas. The study was conducted in the North Hulu Sungai regency of South Kalimantan with the aim of studying the potential of swamp buffalo maintenance areas, assessing the constraints and impacts of swamp buffalo development efforts, determining the logic of the relationship between the problem of swamp buffalo development, compiling a Logical Framework Approach for problem solving (solution) the development of swamp buffalo, making the right strategy for the development of swamp buffaloes that involve the participation of farmers, the private sector, banks, local governments, and higher education institutions on an ongoing basis. Research design with descriptive and participatory methods with LQ analysis techniques, analysis of regional potential, and Logical Framework Analysis (LFA). The results show that swamp agroecological zones are very beneficial for swamp buffalo cultivation, the strategic role of meat producers, labor, sources of income, advocates of sources of animal protein, sources of seeds, tourist attraction, and development of local wisdom. Comparing between the LQ value of 2.327 and the value of livestock density, the HSU District is the base for developing swamp buffalo cattle. The strategy model of swamp buffalo development in HSU District is to increase the use of appropriate technology, promotion through typical Kal-Sel swamp buffalo tourism events, improve: the role of skilled communities, the role of extension agents and the government, increase capital and cooperative relations between business actors, locations cultivation close to transportation routes, regulating land use, and improving institutional performance